The Influence Of Systematic Risk And Liquidity On Stock Return Levels In Banking Companies Listed On The Indonesia Stock Exchange (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2025)
This study aims to examine the effect of systematic risk and stock liquidity on stock returns. This study is an associative study with a clause approach. The variables used are independent variables, namely systematic risk and liquidity, and the dependent variable, namely stock returns. The population of this study is banking companies listed on the Indonesia Stock Exchange for 5 years (2019 - 2023). The sampling method uses a purposive sampling method with a sample size of 41 companies. The type of data used is secondary data with data collection techniques through documentation. The data analysis technique uses multiple linear regression analysis with the analysis tool used for testing is the Statistical Program for Social Science (SPSS) 25. The results of statistical tests show that systematic risk partially affects the level of stock returns, and liquidity also affects the level of stock returns. Then the results of simultaneous testing show that the variables systematic risk and stock liquidity affect the level of stock returns.